Target Mechanisms of the Cyanotoxin Cylindrospermopsin in Immortalized Human Airway Epithelial Cells - Ziesemer, Sabine; Meyer, Susann; Edelmann, Julia; Vennmann, Janita; Gudra, Celine; Arndt, Denise; Effenberg, Marcus; Hayas, Olla; Hayas, Aref; Thomassen, Johanna Sophia; Kubickova, Barbara; Pöther, Dierk-Christoph; et al. (Toxins, 2022)
Cylindrospermopsin (CYN) is a cyanobacterial toxin that occurs in aquatic environments worldwide. It is known for its delayed effects in animals and humans such as inhibition of protein synthesis or genotoxicity. The molecular targets and the cell physiological mechanisms of CYN, however, are not well studied. As inhalation of CYN-containing aerosols has been identified as a relevant route of CYN uptake, we analyzed the effects of CYN on protein expression in cultures of immortalized human bronchial epithelial cells (16HBE14o-) using a proteomic approach. Proteins whose expression levels were affected by CYN belonged to several functional clusters, mainly regulation of protein stability, cellular adhesion and integration in the extracellular matrix, cell proliferation, cell cycle regulation, and completion of cytokinesis. With a few exceptions of upregulated proteins (e.g., ITI inhibitor of serine endopeptidases and mRNA stabilizer PABPC1), CYN mediated the downregulation of many proteins. Among these, centrosomal protein 55 (CEP55) and osteonectin (SPARC) were significantly reduced in their abundance. Results of the detailed semi-quantitative Western blot analyses of SPARC, claudin-6, and CEP55 supported the findings from the proteomic study that epithelial cell adhesion, attenuation of cell proliferation, delayed completion of mitosis, as well as induction of genomic instability are major effects of CYN in eukaryotic cells.
Keywords: proteomics; Cyanobacteria Toxins; cell cycle; cytokinesis; extracellular matrix; proteiny buněčného cyklu; lidé; proteomika; Cell Cycle Proteins; cylindrospermopsin; epitelové buňky; Proteomics; cyanotoxin; toxiny kmene Cyanobacteria; Epithelial Cells; Humans; airway epithelial cells